Virus-like particle: a nano-platform that delivers cancer antigens to elicit an anti-tumor immune response - Ning, Weisen; Yan, Sheng; Song, Yongyao; Xu, Hanning; Zhang, Jinling; Wang, Xiaomei (Frontiers in Immunology, 2025)
Virus-like particles (VLPs), as a unique form of nanocarrier, predominantly encompass hollow protein shells that exhibit analogous morphology and structure to naturally occurring viruses, yet devoid of genetic material. VLPs are considered safe, easily modifiable, and stable, making them suitable for preparation in various expression systems. They serve as precise biological instruments with broad applications in the field of medical biology. Leveraging their unique structural attributes and facile modification capabilities, VLPs can serve as an effective platform for the delivery of tumor antigens, thereby stimulating the immune system and facilitating the eradication of tumor cells.